Global Economic Prospects, June 2017 : A Fragile Recovery - World Bank Group (Washington, DC: World Bank, 2017)
Global activity is firming broadly as expected. Manufacturing and trade are picking up, confidence is improving, and international financing conditions remain benign. Global growth is projected to strengthen in 2018-19, in line with January forecasts. In emerging market and developing economies (EMDEs), growth is predicted to recover in 2017-19, as obstacles to growth in commodity exporters diminish amid moderately rising commodity prices, and activity in commodity importers remains robust.